1997
DOI: 10.1021/ja964477f
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Dimerization and Membrane Anchoring in Activity of Glycopeptide Antibiotics against Vancomycin-Resistant Bacteria

Abstract: The mode of action of a semisynthetic glycopeptide active against vancomycin-resistant bacteria has been investigated. It is shown that the antibiotic, biphenylchloroeremomycin or LY307599, dimerizes strongly and anchors to membranes. It is hypothesized that these two locating devices, previously identified by us when acting separately, might combine to give enhanced binding at a cell surface. This hypothesis is tested experimentally by showing that glycopeptides can bind cell-wall precursor analogues from res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 38 publications
1
69
0
2
Order By: Relevance
“…Therefore, the chlorobiphenyl substituent attached to the disaccharide somehow confers transglycosylase inhibitory activity onto the glycopeptide analogue. We do not believe that the effects of the chlorobiphenyl group are related to nonspecific hydrophobic interactions because the damaged teicoplanin derivative (6), which also contains a lipid-substituted carbohydrate moiety, does not have transglycosylase inhibitory activity.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the chlorobiphenyl substituent attached to the disaccharide somehow confers transglycosylase inhibitory activity onto the glycopeptide analogue. We do not believe that the effects of the chlorobiphenyl group are related to nonspecific hydrophobic interactions because the damaged teicoplanin derivative (6), which also contains a lipid-substituted carbohydrate moiety, does not have transglycosylase inhibitory activity.…”
Section: Resultsmentioning
confidence: 93%
“…Although free in solution vancomycin is only dimeric at millimolar concentrations, dimerization is believed to be clinically important. Several groups have noted that there is a general correlation between the propensity of glycopeptides that target lipid II to dimerize and their ability to bind both to model bacterial membranes and to bacterial cell walls [31,32]. Moreover, the activity of covalently linked vancomycin dimers is normally higher than that of the monomer [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The Nsubstituted derivatives of LY264826 are even more strongly dimerized, with the extent of dimerization apparently determined by the nature of the side chain (3). The N-substituted derivatives also demonstrate a greater tendency to interact with bacterial membranes, a process that could serve to anchor these agents at the in vivo target site (2,3,5,6,11,37). Our studies (3) revealed a relatively high degree of correlation between the extent of dimerization of glycopeptide antibiotics and antibacterial activity and a very high degree of correlation between antibacterial activity and the concentration of a DAla-D-Ala-containing tripeptide ligand needed in the growth medium to antagonize antibacterial activity.…”
mentioning
confidence: 99%
“…These kinds of interactions are not predicted by estimating association constants in free solution. However, the contribution of intramolecular effects to the binding of glycopeptide antibiotics to D-Ala-D-Ala and D-Ala-D-Lac residues at the bacterial surface has been demonstrated by nuclear magnetic resonance and surface plasmon resonance techniques with a variety of model systems, namely, phosphatidylcholine vesicles (13,37), lipid monolayers (10,11), and a whole-cell antagonist binding assay (5).…”
mentioning
confidence: 99%